2020
DOI: 10.1186/s12889-020-08760-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of fatal car accident risk in Finote Selam town, Northwest Ethiopia

Abstract: Background: In the globe, 1.3 million deaths and around 50 million non-fatal injuries were reported. From all deaths, 90% occur in developing countries. Ethiopia is considered as one of the worst countries in the globe where road traffic accident causes a lot of fatalities and injuries of road users every year. The main objective of the study was to identify the main predictors of fatal car accident. Methods: The retrospective research design was applied. 255 records were taken from Finote Selam traffic police… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
4
12
2
Order By: Relevance
“…Our study results indicate 91.8% of drivers involved in RTAs were males, while females share only 1.7% of the total reported RTA. This finding is in line with findings in previous studies in northern Ethiopia by ( 11 ) which reported that 99.6% of drivers involved in RTAs were male. It also agrees with finding of ( 10 , 12 ) who reported that majority of RTA victims were males in Amhara and Southern National Regional States of Ethiopia.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study results indicate 91.8% of drivers involved in RTAs were males, while females share only 1.7% of the total reported RTA. This finding is in line with findings in previous studies in northern Ethiopia by ( 11 ) which reported that 99.6% of drivers involved in RTAs were male. It also agrees with finding of ( 10 , 12 ) who reported that majority of RTA victims were males in Amhara and Southern National Regional States of Ethiopia.…”
Section: Discussionsupporting
confidence: 93%
“…Different studies considered driving license ownership as a key determinant of studying RTA ( 11 , 34 , 35 ). As the result shown in Table 1 , 106(25.4%) of RTA was reported from drivers who were driving without license while 48(11.5%) of RTA was reported from drivers had forged or non-equivalent driving license.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Male drivers, alcohol/drug use, exceeding the speed limit, under-maintained vehicles, night-time driving, and poor road and traffic management are factors increasing the severity of an event. Using personal restraints (seatbelt/helmet), safer vehicles and improved road hazard treatment are preventive measures during the event; first aid, rescuer skills, and accessibility of rescue teams are preventive measures post-event [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. While factors influencing the severity outcome were well-established in previous research, most of the literature only focused on local road users.…”
Section: Introductionmentioning
confidence: 99%